2010
DOI: 10.1038/oby.2009.167
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and SCFA in Lean and Overweight Healthy Subjects

Abstract: articles epidemiology led to the hypothesis that Methanobrevibacter smithii may be a therapeutic target for the reduction of energy harvest in obese humans (25,26), as M. smithii is the major representative of the human gut methanogens (27).The purpose of this study was to investigate whether the proposed role of SCFA and microbiota composition in obesity, which was based on proof of principle experiments, can be confirmed in a larger study which did not exclude all confounding factors. Methods and Procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

142
1,579
41
72

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 2,141 publications
(1,834 citation statements)
references
References 44 publications
142
1,579
41
72
Order By: Relevance
“…Our results are consistent with human studies 35. Schwiertz et al36 analyzed fecal microbiota by real‐time polymerase chain reaction (RT‐PCR) instead of pyrosequencing and observed that the proportion of Bacteroidetes was increased in the fecal microbiota of obese humans. Other studies observed no differences in the proportions of Bacteroidetes and Firmicutes in lean and obese individuals 37, 38.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with human studies 35. Schwiertz et al36 analyzed fecal microbiota by real‐time polymerase chain reaction (RT‐PCR) instead of pyrosequencing and observed that the proportion of Bacteroidetes was increased in the fecal microbiota of obese humans. Other studies observed no differences in the proportions of Bacteroidetes and Firmicutes in lean and obese individuals 37, 38.…”
Section: Discussionsupporting
confidence: 91%
“…The significantly higher concentration of SCFAs in obese participants in our study may indicate that in obese children colonic fermentation is elevated, or alternatively that there is decreased SCFA absorption due to low‐grade inflammation or more rapid gut transit. This has previously been observed in cohorts of both children (Payne et al ., 2011) and adults (Schwiertz et al ., 2009; Fernandes et al ., 2014). Elevated fecal concentrations of total or individual SCFAs might result from increased microbial production, shifts in microbial cross‐feeding patterns or low mucosal absorption (Schwiertz et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This has previously been observed in cohorts of both children (Payne et al ., 2011) and adults (Schwiertz et al ., 2009; Fernandes et al ., 2014). Elevated fecal concentrations of total or individual SCFAs might result from increased microbial production, shifts in microbial cross‐feeding patterns or low mucosal absorption (Schwiertz et al ., 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations